Risk Factors for Benign Convulsions With Mild Gastroenteritis - Fang, Cuiyun; Fan, Wei; Zhang, Chunsheng; Yang, Yi (Frontiers in Pediatrics, 2022)
Objective: To investigate the risk factors for benign convulsions with mild gastroenteritis (CwG) and provide a basis for the early identification and diagnosis. Method: We selected children with CwG and acute gastroenteritis in the same period who attended the pediatric department of the Liyang People's Hospital from June 2018 to June 2021. A retrospective analysis of the general data, clinical characteristics, and laboratory test results of the two groups was performed. Finally, we conducted a multifactorial logistic regression analysis to derive the risk factors for CwG. Results: A total of 82 children were included in the CwG and 93 children were included in the acute gastroenteritis group. Univariate analysis showed no significant differences in gender, age, vomiting, diarrhea, neutrophil, lymphocyte, hemoglobin, platelets, and serum calcium. Statistically significant differences were found in onset season, rotavirus, white blood cells, aspartate aminotransferase, alanine transaminase, serum sodium, and uric acid. Finally, multifactorial logistic regression analysis showed rotavirus (OR, 3.042, 95% CI, 1.116-8.289, p = 0.030), serum sodium (OR, 0.811, 95% CI, 0.684-0.962, p = 0.016) and uric acid (OR, 1.018, 95% CI, 1.012-1.024, p = 0.000) to be independent risk factors. Conclusion: Characteristics of gastroenteritis symptoms such as vomiting and diarrhea cannot be used to predict the onset of CwG. Rotavirus is an independent risk factor for CwG, and decreased serum sodium and increased uric acid can be used as early warning indicators for CwG.